Effects of supportive-educative program on quality of life of adolescents living with a parent with cancer - Mehrdad Azarbarzin; Azadeh Malekian; Fariba Taleghani (Wolters Kluwer Medknow Publications, 2015)
Background: Cancer has significant traumatic effects on the family members of the patients, particularly in Asia's tightly knitted families. Research evidence suggests a debilitating impact of cancer on the quality of life of the afflicted individuals, their spouses, and their families. Since a few studies have been carried out on the quality of life of adolescents living with parents diagnosed with cancer, especially in Iran, the research team decided to evaluate the quality of life of them and also investigate the effects of supportive-educative program on it. Materials and Methods: The present quasi-experimental, one-group study had a pre-test-post-test design and was performed in Esfahan in 2014. The sample of this study consisted of 30 adolescents. The data gathering tool was the short form of quality of life questionnaire (SF-36). Data were analyzed by descriptive statistics and paired sample t-test. P-value of 0.05 was considered significant. Results: The paired sample t-test showed that before and after presenting the program, there were significant statistical differences in some aspects of quality of life, such as physical functioning (P = 0.01), energy/fatigue (P < 0.0001), emotional well-being (P < 0.0001), social functioning (P = 0.001), pain (P < 0.0001), and general health (P = 0.01). Conclusions: This research showed that supportive-educative program can enhance some aspects of quality of life. Therefore, nurses and other health professionals can use this scheme or similar programs for helping adolescents living with a parent with cancer.